Staying ahead of the global pack : [creating sustainable competitive advantage in the marketing of South African table grapes to the United Kingdom in the deregulated era] - Symington, Stuart (School of Economics, 2014)
Includes abstract. Includes bibliographical references (leaves 220-237).